2012
DOI: 10.2337/dc12-0614
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase Is an Early Biomarker of Inflammation and Cardiovascular Risk in Prepubertal Obese Children

Abstract: OBJECTIVEObesity is associated with a state of chronic low-grade inflammation. Myeloperoxidase (MPO) plays an important role in the initiation and progression of acute and chronic inflammatory diseases, such as cardiovascular disease (CVD). The objectives of the current study were to evaluate plasma MPO levels in prepubertal obese children and to determine whether MPO could be an early biomarker of inflammation and CVD risk.RESEARCH DESIGN AND METHODSIn a prospective multicenter case-control study paired by ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 26 publications
9
70
3
1
Order By: Relevance
“…Besides that, the results of our study revealed the suppressive effect of caffeine on the hepatic content of MPO, which comes into agreement with results of previous work [25]. MPO is an early biomarker of inflammation, which plays an important role in the initiation and progression of acute and chronic inflammatory diseases [26].…”
Section: Discussionsupporting
confidence: 93%
“…Besides that, the results of our study revealed the suppressive effect of caffeine on the hepatic content of MPO, which comes into agreement with results of previous work [25]. MPO is an early biomarker of inflammation, which plays an important role in the initiation and progression of acute and chronic inflammatory diseases [26].…”
Section: Discussionsupporting
confidence: 93%
“…Prepubertal obese children [129] showed an elevation of proinflammatory factors (TNF-alpha, IL-6, CPR, PAI-1), and markers of endothelial dysfunction which contribute to early increase of cardiovascular diseases later in life. Likewise, serum myeloperoxidase (MPO) level was elevated in prepubertal obese children [129].…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Likewise, serum myeloperoxidase (MPO) level was elevated in prepubertal obese children [129]. MPO is an enzyme which has bactericidal action and plays an important role in the onset and progression of acute and chronic inflammatory diseases.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…MPO levels showed strong positive correlation with HbA1C, HOMA-IR, FPG ,PPG, cholesterol , LDL and also negative correlation was observed between HDL cholesterol. Chronic high concentrations of glucose and dyslipidemias cause oxidative stress and along with proinflammatory mediators may impair insulin signaling, initiates insulin resistance [20][21][22]. MPO protein abundantly expressed in polymorphonuclear neutrophils (PMNs) and monocytes, is also a catalyst of 3-nitrotyrosine (NO 2 Tyr) formation via nitrite oxidation to the potent nitrating species nitrogen dioxide (•NO 2 ) [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%